Implementation of Criminal Sanctions by Public Prosecutor against Narcotics Abuse - Prihananto Prihananto; Anis Mashdurohatun (Universitas Islam Sultan Agung, 2020)
The purpose of this study is to describe and analyze the implementation, barriers and policies to overcome obstacles in the application of criminal sanctions by public prosecutors in prosecuting class I narcotics abusers at the Semarang City District Attorney. The method used in this research is juridical empirical, which is descriptive-analytical. The data used in this study are primary data and secondary data, which were obtained from interviews and literature studies, then analyzed qualitatively. The conclusions in this study are: (1) the application of criminal sanctions by the public prosecutor refers to the BAP and evidence provided by the police, which is based on the activities of the suspect when the police are arrested; (2) obstacles in the implementation of the application of criminal sanctions by the public prosecutor, including obstacles in terms of legal substance, legal structure and legal culture: (3) so that policies are needed to overcome these obstacles to achieve justice, including revision of articles in the Law. Narcotics Law, holding knowledge sharing, holding outreach, and coordinating with related agencies.